Nanocomposite-Based Electronic Tongue : Carbon Nanotube Growth by Chemical Vapor Deposition and Its Application - TermehYousefi, Amin (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the fabrication of a frequency-based electronic tongue using a modified glassy carbon electrode (GCE), opening a new fi eld of applying organic precursors to achieve nanostructure growth. It also presents a new approach to optimizing nanostructures by means of s tatistical analysis. The chemical vapor deposition (CVD) method was ut ilized to grow vertically aligned carbon nanotubes (CNTs) with various aspect ratios. To increase the graphitic ratio of synthesized CNTs, seq uential experimental strategies based on response surface methodology w ere employed to investigate the crystallinity of CNTs. In the next step , glucose oxidase (GOx) was immobilized on the optimized multiwall carb on nanotubes/gelatin (MWCNTs/Gl) composite using the entrapment techniq ue to achieve enzyme-catalyzed oxidation of glucose at anodic potential s, which was drop-casted onto the GCE. The modified GCE's performance i ndicates that a GOx/MWCNTs/Gl/GC electrode ca n be utilized as a glucos e biosensor with a high direct electron transfer rate between GOx and M WCNTs/Gl. It was possible to use the fabricated biosensor as an electro nic tongue thanks to a frequency-based circuit attached to the electroc hemical cell. The results indicate that the modified GCE (with GOx/MWCN Ts/Gl) holds promising potential for application in voltammetric electr onic tongues.
Introduction -- Literature Review -- Experimental Procedures and Mat erials -- Results and Discussions -- Conclusions.
Description based on publisher-supplied MARC data.
Keywords: Biological physics; Biomedical engineering; Biophysics; Electronic materials; Nanoscale science; Nanoscience; Nanostructures; Optical materials; Physical chemistry; Optical and Electronic Materials; Biological and Medical Physics, Biophysics; Biomedical Engineering and Bioengineering; Nanoscale Science and Technology; Physical Chemistry